2010
DOI: 10.1177/0018726709345043
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of and reactions to workplace bullying: A social exchange perspective

Abstract: The aim of this article is to introduce a social exchange perspective to the study of workplace bullying. Much of the existing research on bullying has had a strong empirical focus, leaving the concept relatively under-theoretized. By applying the social exchange theory based concepts of justice, psychological contract breach, and perceived organizational support, we aim to shed light on a number of aspects of bullying that to date have remained poorly understood. First, drawing on the concepts of justice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
272
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(293 citation statements)
references
References 86 publications
(101 reference statements)
11
272
0
10
Order By: Relevance
“…Theoretical development in the WPB literature has been described as weak (Blasé & Blasé, 2002;Parzefall & Salin, 2010;Samnani, 2013). Researchers have however, drawn on a variety of theoretical frameworks, such as the social exchange theory (Parzefall & Salin, 2010), a work environment framework (Hauge et al, 2007), Bronfenbrenner's ecological systems theory (De Wet, 2010), critical management theory (Samnani, 2013), social dominance theory (SDT) (Parkin, Fishbein & Richey, 2006), job demands-resources model (Van den Broeck et al, 2011) and symbolic interactionism (Blasé & Blasé, 2002;Samnani, 2013) to frame and understand bullying behaviour.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Theoretical development in the WPB literature has been described as weak (Blasé & Blasé, 2002;Parzefall & Salin, 2010;Samnani, 2013). Researchers have however, drawn on a variety of theoretical frameworks, such as the social exchange theory (Parzefall & Salin, 2010), a work environment framework (Hauge et al, 2007), Bronfenbrenner's ecological systems theory (De Wet, 2010), critical management theory (Samnani, 2013), social dominance theory (SDT) (Parkin, Fishbein & Richey, 2006), job demands-resources model (Van den Broeck et al, 2011) and symbolic interactionism (Blasé & Blasé, 2002;Samnani, 2013) to frame and understand bullying behaviour.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Researchers have however, drawn on a variety of theoretical frameworks, such as the social exchange theory (Parzefall & Salin, 2010), a work environment framework (Hauge et al, 2007), Bronfenbrenner's ecological systems theory (De Wet, 2010), critical management theory (Samnani, 2013), social dominance theory (SDT) (Parkin, Fishbein & Richey, 2006), job demands-resources model (Van den Broeck et al, 2011) and symbolic interactionism (Blasé & Blasé, 2002;Samnani, 2013) to frame and understand bullying behaviour. In this study we draw upon one of the most widely known and comprehensive frameworks of WPB proposed by Einarsen et al (2011), and SDT (Pratto & Stewart, 2012) to study the perpetrators of WPB in schools.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on social workers showed that it was hard for them to align their personal experiences with bullying in the workplace to the principles and values they associate their work with, and this made them view their workplaces as hypocritical [48]. Bullying in itself can be viewed as a stressor and a violation of trust [50,51]. Trust violations in the workplace can be interpreted as violations of the psychological contract between employer and employee and lead to perceptions of injustice among both targets and observers according to the social exchange perspective [51], thereby undermining the organization's social capital.…”
Section: Introductionmentioning
confidence: 99%